Critical Assessment Of Nursing Profession In Saudi Arabia: With Reference To Work Environment (The Review of Diabetic Studies, 2024)
Promoting nursing as a viable career path that many people can pursue is one of the Ministry of Health's objectives; in order to achieve Vision 2030 in Saudi Arabia, a healthy practice environment is necessary to improve patient care and nurse retention rates. The World Health Organization claims that there is a global shortage of health professionals, with nurses and midwives making up over half of the need. This present study will evaluate the scenario with a primary data approach using a detailed questionnaire, which will be exercised with the selected set of nurses in hospitals of Makkah city.